Merit students encyclopedia 2026-02-15T21:52:55+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Friedman, Emanuel; Halsey, William Darrach, 1918- (Macmillan Educational Co ; Collier, 1982)

(untitled)
Encyclopedia entries are designed for students from fifth grade through high school and are written or reviewed by subject specialists